P‐168: High Efficiency (EQE>30%) TADF‐OLED with Lightly‐doped Emitter (0.5%) by using TADF‐Host. Issue 1 (25th September 2020) - Ding, Wen-Cheng; Huang, Jau-Jiun; Chen, Chia-Hsun; Chiu, Tien-Lung; Lin, Chi-Feng; Leung, Man-Kit; Lee, Jiun-Haw
Abstract : High efficiency (EQE=30.15%) organic light emitting diode (OLED) was demonstrated by lightly doping the thermally activated delayed fluorescence (TADF) emitter (0.5%) into the TADF host, resulting from: (1) efficient energy transfer from host to dopant, (2) long exciton diffusion length in host, and (3) rare concentration quenching due to lightly‐doped condition.